God, memory and beauty: A Manichaean analysis of Augustine"s Confessions , Book X - Oort, Johannes van (HTS teologiese studies, 2013)
The article first sketches some main trends in the recent study of Augustine’s Confessions as a work aimed at Manichaean readers. It then detects and analyses the Manichaean-inspired parts in Book X of the Confessions. Augustine’s famous theory of memory seems to be directly inspired by Manichaean concepts such as found in the Coptic Manichaean Kephalaia. The article end with a number of conclusions.